Child development booklet on maternal knowledge in golden age children - Rahayu, Yuyun; Sukmawati, Ima; Nur Fauziyah, Dini; Anugrah Pauji Salam, Wulan (Science Midwifery, 2024)
The Golden Age is a very effective and urgent period for optimizing the various intelligence potentials possessed by children. The success of developing a child's intelligence lies in the level of knowledge of parents, especially mothers, in utilizing opportunities during the growth and development period. Child Development Booklet is one of the solutions in improving maternal intelligence. The purpose of this study was to see the level of knowledge of mothers before and after being given the Child Development Booklet. The method in this study is quantitative using one group with a pretest postest design approach, with a research sample of 71 mothers. The research was conducted in May-June 2024 at PKM Ciamis. The results showed that the frequency of pre-test knowledge level was 36.6% and the post-test results showed a percentage increase of 46.5% to 83.1%. In the sufficient category, a percentage decrease was obtained from 28.2% to 16.9%. While for the less category showed a decrease of 35.2%. The conclusion in the study is that there is an increase in maternal knowledge after being given a child development booklet with an average respondent in the good category.